Silas's seven grandparents - Horrocks, Anita, 1958- (Orca Book Publishers, 2010)
Silas' Seven Grandparents is a fun and loving story about having multiple sets of grandparents and stepgrandparents. When Silas' parents go away on a business trip, all seven grandparents invite Silas to stay with them. How can he choose one without hurting the others' feelings?